Role of Entangled Stakeholders in the Development of Indonesia Digital Creative Ecosystem - Cici Cintyawati (Universitas Islam Bandung, 2019)
ABSTRACT Digital creative industry in Indonesia growth rapidly in the last few years. This opportunity leads Indonesian central government declare a new vision to make Indonesia as the largest digital economy in ASEAN in 2020. To reach that vision, the first thing to do is build the digital creative ecosystem by integrating entangled stakeholders. By considering to this issue, this research was conducted to: (1) get deeper information about the digital creative ecosystem in Indonesia, (2) identify the roles of stakeholders in the digital creative ecosystem, and (3) analyze the role of stakeholders using service science perspective. Exploratory research was chosen to give better understanding related the types of issues happened in the ecosystem. Five key stakeholders were selected as informants so they can share their opinions and perspectives related to their role in the ecosystem. Strategic Options Development and Analysis then be used to analyze the transcribed interview. The result shows two major issues appeared in the digital creative ecosystem, which are collaboration and business ecosystem issues. It is found that there are four major roles in the digital creative industry: keystone, dominator, hub landlords, and niche player role. Association is expected to become the keystone to develop the ecosystem by sharing values with other stakeholders. Keywords: Stakeholder’s Role, Strategic Options Development and Analysis, Digital Creative Industry, Service Science ABSTRAK Industri kreatif digital di Indonesia tumbuh pesat dalam beberapa tahun terakhir. Peluang ini membuat pemerintah pusat Indonesia mendeklarasikan visi baru untuk menjadikan Indonesia sebagai ekonomi digital terbesar di ASEAN pada tahun 2020. Untuk mencapai visi itu, hal pertama yang harus dilakukan adalah membangun ekosistem kreatif digital dengan mengintegrasikan para pemangku kepentingan yang terkait. Dengan mempertimbangkan masalah ini, penelitian ini dilakukan untuk: (1) mendapatkan informasi lebih dalam tentang ekosistem kreatif digital di Indonesia, (2) mengidentifikasi peran pemangku kepentingan dalam ekosistem kreatif digital, dan (3) menganalisis peran pemangku kepentingan menggunakan perspektif ilmu layanan. Penelitian eksplorasi dipilih untuk memberikan pemahaman yang lebih baik terkait jenis masalah yang terjadi di bidang yang diteliti. Lima pemangku kepentingan utama dipilih sebagai informan sehingga mereka dapat membagikan pendapat dan perspektif mereka terkait dengan peran mereka dalam ekosistem kreatif digital. Pengembangan Opsi Strategis dan Analisis kemudian digunakan untuk menganalisis wawancara yang ditranskripsi. Hasilnya menunjukkan dua masalah utama muncul dalam ekosistem kreatif digital, yaitu kolaborasi dan masalah ekosistem bisnis. Ditemukan bahwa ada empat peran utama dalam industri kreatif digital: keystone, dominator, tuan tanah hub, dan peran pemain khusus. Asosiasi diharapkan menjadi keystone untuk mengembangkan ekosistem kreatif digital dengan berbagi nilai dengan pemangku kepentingan lainnya. Kata Kunci: Peran Stakeholder, Pengembangan Strategic Options dan Analisisnya, Industri Digital Creative, Service Science